Assistance for SMEs in Obtaining Business Legality through OSS RBA in Cimahi City West Java - Mulyeni, Sri; Handayani, Rini; Shiyammurti, Nastiti Rizky; Jaenudin, Jejen; Herlina, Herlina (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research investigates the impact of the COVID-19 pandemic on Micro, Small, and Medium Enterprises (MSMEs) in Cimahi City, West Java, and evaluates government efforts to support their recovery by simplifying the business legality process through the Online Single Submission Risk Based Approach (OSS-RBA) application. Method: Employing a mixed-methods approach, quantitative data on MSMEs' pandemic impact and qualitative insights into the OSS-RBA application's efficacy are collected via surveys, reports, interviews, and focus groups. The analysis involves statistical techniques and thematic analysis. Practical Applications: The study informs policymakers, stakeholders, and MSMEs on leveraging digital solutions like OSS-RBA for smoother permit acquisition. It suggests refining support mechanisms and targeted interventions to bolster the resilience of MSMEs amidst challenges. Conclusion: Government support and digital solutions like OSS-RBA are crucial for MSME recovery post-pandemic. Recommendations aim to enhance the business environment and foster sustainable local development.